SOPANA MUSIC OF KERALA: A STUDY ON THE DECAYING TRENDS - Soumya. S
From time immemorial, the splendid and vivacious culture of Kerala lured the people throughout the world. Its rich heritage is known by its songs and dances, ballads, rituals and intellectual pursuits. The soul stirring music known as “Sopana” (Ashtapadi singing) is a part of music ritual in a number of temples in Kerala. Sopana Sangeetham is as old as the establishment of the tantric way of worship in the Kerala Temples. Art was considered sacred and artists had a lot of respect in the society. But sadly, from the beginning of the twentieth century, traditions have slowly been compromised and due to the change in people’s lifestyle and advancement in science and technology, a number of art forms slowly died. Very few temples today continue to observe the music traditions that were followed by their forefathers. There are only 86 ardent practitioners of Sopana Sangeetham in the state for one lakh odd temples, sacred groves and other religious places. It will really be a pity if, with the advance of civilization these artistic and ceremonial rituals are forgotten and lost